Punishment for inland water pollution under the Environmental Quality (Industrial effluent) Regulation 2009 - Yaacob, Nurli; Abdul Wahab, Harlida; Mohd Anuar, Haslinda (Global Academic Excellence, 2018)
Inland water pollution becomes an important issue today. Furthermore, if this pollution is carried out by a large business organization and able to pay the penalty in the form of money. There is a legal framework governing the inland water pollution penalties, namely the Environmental Quality Act 1974 and its regulations including the Environmental Quality (Industrial Effluent) Regulations 2009. Therefore, this article was written to study the provisions of the law under the Environmental Quality (Industrial Effluent) Regulations 2009 as well as kind of punishment from cases that have been decided by the court in respect ofinland water pollution on companies. The findings show that the punishment provided by law is sufficient. However, the fine imposed by the court is relatively low and the percentage of cases which involved imprisonment is extremely small.